Electromagnetic Waves Can Help Improve the Rate of Increase of Milk Feeds Per Day in Premature Infants With Necrotizing Enterocolitis: A Pilot Trial - Xuexiu Liu; Xuexiu Liu; Xuexiu Liu; Xianhong Zhang; Xianhong Zhang; Xianhong Zhang; Luquan Li; Luquan Li; Luquan Li; Jianhui Wang; Jianhui Wang; Jianhui Wang; et al. (Frontiers Media S.A., 2022)
ObjectiveTo evaluate the effects of electromagnetic waves generated by a commercial medical electromagnetic instrument (trade name, TDP, the Chinese phonetic abbreviation of "Te-ding Dian-ci-bo Pu") as an adjuvant to improve the rate of increase of milk feeds per day by premature infants with necrotizing enterocolitis (NEC).MethodsThis study was a prospective randomized clinical trial. A total of 103 premature infants were diagnosed with NEC II, but there was no need for surgery. The infants were randomly divided into the TDP intervention group and the control group by a randomized method using SPSS 24.0. The patients in the TDP intervention group were treated with TDP irradiation and routine interventions; those in the control group were treated with routine interventions. The rate of increase of milk feeds per day, the time to achieve total gastrointestinal nutrition, the velocity of weight gain, and the complication incidence rate were recorded and compared.ResultsThe rate of increase of milk feeds per day in the TDP intervention group was significantly greater than that in the control group [14.51 (11.58~22.11) ml/kg/d vs. 10.15 (6.15~15.87) ml/kg/d, P = 0.002]. Compared to the control group, the time to achieve total gastrointestinal nutrition (21.45 ± 1.87 d vs. 36.43 ± 2.585 d, P = 0.000) and the velocity of weight gain (19.65 ± 15.27% vs. 13.68 ± 7.15%, P = 0.013) in the TDP intervention group were substantially better than those in the control group. The complication incidence rate was not significantly different between the two groups (P > 0.05).ConclusionTreatment with TDP-generated electromagnetic waves improved the volume of milk consumed per day in premature infants with NEC II and were conducive to improving their clinical outcomes.